The performances photodiode and diode of ZnO thin film by atomic layer deposition technique. (December 2016) - Orak, İkram
Abstract: In this study, the photodiode and diode characterizations of Al/n-ZnO/p type Si heterostructure have been investigated with current–voltage (I–V), capacitance–voltage (C–V) and conductance–voltage (G/ω–V) measurements. ZnO thin film has been deposited on p type Si by using atomic layer deposition technique. Some photodiode and diode parameters such as open circuit voltage ( Voc ), short circuit current ( Isc ), power efficiency( η P ), fill factor ( FF ), ideality factor ( n ) and barrier height ( Φb ) have calculated with I–V and C–V characteristics. Voc and Isc was found to be 0.094 V and 0.24 mA, respectively at 50 mW/cm 2 . n and Φb have been calculated 0.41 eV and 2.36, respectively. Especially, Negative capacitance has explained in the forward bias regions at room temperature and in dark condition. The C–V characterization of the Al/ZnO/p type Si heterostructure has been investigated under illumination condition. It can be said that the capacitance of device has been affected under illumination condition. Highlights: The thin film structure was deposited by atomic layer deposition method. ZnO thickness required both photodiode and diode. The capacitance of device is effected on illumination conditions. Isc, Voc, FF and np were calculated and found to be 242 uA, 92 mV, 33% and 0.18%, respectively.